2012
DOI: 10.7124/bc.000034
|View full text |Cite
|
Sign up to set email alerts
|

Kombucha microbiome as a probiotic: a view from the perspective of post-genomics and synthetic ecology

Abstract: Probiotics are essential for establishing and maintaining optimal immune health. The probiotic therapy is known from alternative medicine for ages; however, the recent demonstration of the normal microflora to induce innate immunity has introduced the science-based concept of therapeutic application of potentially beneficial probiotic microorganisms for a treatment of functional disorders. Traditionally, probiotics are associated with dairy products, however, novel formulations are needed, first of all, origin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 71 publications
0
37
0
6
Order By: Relevance
“…The presence of both Gluconacetobacter and Lactobacillus spp. may also contribute to the fact that the antioxidant activity of the beverages was primarily imparted due to the metabolic activities of these two microbial genera as shown by previous studies [12,21,22]. Figure 1 shows the pH values of the samples on days 0, 1, and 7 as well as the results when the fermented samples are subjected to pancreatic and duodenal digestion.…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…The presence of both Gluconacetobacter and Lactobacillus spp. may also contribute to the fact that the antioxidant activity of the beverages was primarily imparted due to the metabolic activities of these two microbial genera as shown by previous studies [12,21,22]. Figure 1 shows the pH values of the samples on days 0, 1, and 7 as well as the results when the fermented samples are subjected to pancreatic and duodenal digestion.…”
Section: Resultsmentioning
confidence: 74%
“…present in all three pellicles may possess potential therapeutic properties including acting as a probiotic organism. Such microorganisms are known to provide a balance in intestinal microbiota, normalizing processes in gut and boosting the immune system [21]. The presence of both Gluconacetobacter and Lactobacillus spp.…”
Section: Resultsmentioning
confidence: 99%
“…Milk fermentation in colder climates promotes the growth of mesophilic bacteria such as Lactococcus and Leuconostoc, whereas beverages produced at higher temperatures usually have greater counts of thermophilic bacteria such as Lactobacillus and Streptococcus [66,67]. Most often the probiotic bacteria come from Lactobacillus or Bifidobacterium or a cocktail of both [68].…”
Section: Fermented Beverages Containing Probioticsmentioning
confidence: 99%
“…Kombucha beverage is becoming increasingly popular around the world today as a prophylactic probiotic and healing agent [26], and both the kombucha brewed drink and processed pellicles may be promising probiotic/synbiotic formulations [27]. The presence of tea polyphenols, gluconic acid, glucuronic acid, lactic acid, vitamins, minerals in the brewed drink and cellulose pellicle was reported [26].…”
Section: The Dna Metabarcoding Of a Modified Kombucha Microbial Consomentioning
confidence: 99%
“…Kombucha culture is an example of a multi-microbial community with strong mutualistic relationships between its members -bacteria and yeasts. The studies on cultures have revealed that Kombucha Microbial Community (KMC) may include a variety of yeast species and acetobacteria (reviewed in [27]). During the fermentation of sugar in the tea extract the community members produce a big variety of organic molecules, which prevent KMC from colonization by other microorganisms.…”
Section: The Dna Metabarcoding Of a Modified Kombucha Microbial Consomentioning
confidence: 99%